Mortality Risk and The Progression of The Electronic Frailty Index and Hospital Frailty Risk Score Over Time - Joe Hollinghurst; Alan Watkins (International Journal of Population Data Science, 2020)
Introduction The electronic Frailty Index (eFI) and the Hospital Frailty Risk Score (HFRS) have been developed in primary and secondary care respectively.